(untitled) (Journal of Academic Research, 2025)
Motivation plays a vital role in language learning, influencing students’ engagement, participation, and overall success. However, many students in seventh, eighth, and ninth grades in public schools in Misurata, Libya, show a lack of interest in learning English. This study investigates the factors contributing to low motivation among these students and explores potential strategies to enhance their engagement. Using a qualitative research approach, data were collected through semi-structured interviews with 20 English language teachers from five public schools. The findings reveal that traditional teaching methods, a lack of interactive activities, and an overemphasis on grammar and vocabulary significantly hinder student motivation. Additionally, student behaviors such as disengagement, lack of participation, and minimal homework completion further contribute to learning difficulties. Teachers also highlighted challenges such as classroom management issues, curriculum constraints, and the limited real-life application of English. The study suggests incorporating communicative teaching approaches, interactive activities, and multimedia resources to foster a more engaging learning environment. The research highlights the need for professional development programs to equip teachers with effective motivational strategies. These findings contribute to the ongoing discussion on improving English language education in Libya and provide practical recommendations for enhancing student motivation.